Precursor of positive electrode active material and method of producing the same
The precursor for the positive electrode active material, with a radially oriented outer shell and hollow structure, addresses the issue of insufficient Li reaction, resulting in improved output characteristics in lithium ion secondary batteries.
Patent Information
- Application Number
- JP2023114324
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-12
AI Technical Summary
The insufficient reaction with Li during the production of positive electrode active materials leads to inadequate output characteristics in lithium ion secondary batteries.
A precursor for the positive electrode active material is developed, comprising transition metal composite hydroxide particles with a specific structure featuring an outer shell and a hollow portion, where more than 50% of the primary particles are radially oriented, enhancing the reaction area and Li diffusion.
This structure improves the reaction with Li during firing, reducing unreacted Li and enhancing the output characteristics of lithium ion secondary batteries.
Smart Images

Figure 2025011908000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a precursor of a positive electrode active material and a method for producing the same. [Background technology]
[0002] Patent Document 1 discloses a method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery. One of the features of this precursor is that it has a laminated structure in which a center part in which plate-like primary particles are aggregated, a low density part formed by aggregation of fine primary particles, and a high density part formed by aggregation of the plate-like primary particles are laminated on the outside of the center part. Patent Document 2 discloses a precursor for producing a porous positive electrode active material. For example, the positive electrode active material can be produced by mixing the precursor with a Li compound and firing the mixture. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-154143 A [Patent Document 2] JP 2019-021610 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, when a positive electrode active material is produced by firing a precursor of the positive electrode active material, the reaction with Li may be insufficient, resulting in insufficient output characteristics.
[0005] Therefore, a main object of the present disclosure is to provide a technique capable of realizing a lithium ion secondary battery having excellent output characteristics. [Means for solving the problem]
[0006] One aspect of the technology disclosed herein is a precursor of a positive electrode active material used in a lithium ion secondary battery. This precursor contains Ni-containing transition metal composite hydroxide particles, and the transition metal composite hydroxide particles have an outer shell portion in which primary particles having an average aspect ratio (long axis length / short axis length) of 2 or more based on SEM observation are aggregated, and a hollow portion surrounded by the outer shell portion. 50% or more of the primary particles are oriented radially from the center of the transition metal composite hydroxide particle toward the surface, and 90% or more of the primary particles contained in the entire transition metal composite hydroxide particle are present in the outer shell portion.
[0007] The transition metal composite hydroxide particles (also called precursor particles) contained in the precursor have 90% or more of the primary particles present in the outer shell, and have hollows with few or no primary particles. This increases the reactive area of the precursor particles, which improves the reaction with Li during firing and suppresses unreacted Li. In addition, 50% or more of the primary particles in the outer shell are radially oriented, which makes it easier for Li to diffuse and improves output characteristics. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing a cross-sectional structure of a precursor particle of a positive electrode active material according to one embodiment. [Diagram 2] FIG. 2 is a flow diagram showing an outline of a method for producing a positive electrode active material used in a lithium ion secondary battery in one embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing the general configuration of a crystallizer. [Figure 4] FIG. 4 is a schematic cross-sectional view taken along line IV-IV shown in FIG. [Diagram 5] FIG. 5 is a cross-sectional view that illustrates a schematic configuration of a lithium ion secondary battery using the fired product of precursor particles according to one embodiment. [Figure 6] FIG. 6 is a schematic exploded view showing the configuration of the wound electrode body 20. As shown in FIG. [Figure 7] FIG. 7 is a cross-sectional SEM image of the precursor particle of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the technology disclosed herein will be described with reference to the drawings. Note that matters other than those specifically mentioned in this specification and necessary for implementing the present technology (for example, the general configuration and manufacturing process of a lithium ion secondary battery that does not characterize the present technology) can be understood as design matters of a person skilled in the art based on the conventional technology in the field. The present technology can be implemented based on the contents disclosed in this specification and the technical common sense in the field. Note that each drawing is drawn diagrammatically, and the dimensional relationship (length, width, thickness, etc.) does not necessarily reflect the actual dimensional relationship. In addition, in the drawings described below, the same reference numerals are given to members and parts that perform the same function, and duplicated descriptions may be omitted or simplified.
[0010] In this specification, when a numerical range is described as "A to B (where A and B are any numerical values)", it means "A or more and B or less", and also includes the meanings of "greater than A and less than B", "greater than A and B or less", and "greater than A and less than B".
[0011] In this specification, the term "lithium ion secondary battery" refers to any secondary battery that uses lithium ions as a charge carrier and achieves charging and discharging by the transfer of charge associated with lithium ions between positive and negative electrodes, and is a term that also includes lithium ion capacitors and the like.
[0012] The present disclosure provides a precursor material for a positive electrode active material used in a lithium ion secondary battery. The precursor material is, for example, in a powder form. The precursor material includes a plurality of precursor particles. FIG. 1 is a schematic diagram of a cross-sectional structure of a precursor particle 200 of a positive electrode active material according to one embodiment. The precursor particle 200 has a hollow structure including an outer shell portion 210 and a hollow portion 220.
[0013] The precursor material contains precursor particles 200 as the main component. The precursor particles 200 account for, for example, 80 wt% or more, 90 wt% or more, 95 wt% or more, or 100 wt% of the precursor material.
[0014] The precursor particles 200 are particles containing a transition metal composite hydroxide (also referred to as "transition metal composite hydroxide particles 200"). The precursor particles 200 contain a transition metal and preferably contain at least nickel (Ni). The precursor particles 200 are converted into a lithium transition metal composite oxide by being fired in a state where a lithium element (Li element) is supplied. Such a lithium transition metal composite oxide can be used as a positive electrode active material.
[0015] In some embodiments, the precursor particles 200 have the following general formula (i): Ni (1-x-y-z) Co x Mn y A z (OH) 2+a (i) and have a composition represented by. However, in the general formula (i), it is assumed that 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 ≦ z ≦ 0.1, 0 ≦ a ≦ 0.5, and x + y + z < 1 are satisfied. In the general formula (i), A is at least one element selected from the group consisting of Mg, Ca, V, Cr, Al, Ti, Zr, Nb, Mo, and W is at least one element selected from the group.
[0016] In some embodiments, the proportion of Ni is higher than the total proportion of Co and Mn. That is, in the general formula (i), x + y + z < 0.5 may be satisfied.
[0017] In some embodiments, the precursor particles 200 contain Ni, Co, and Mn. That is, in the general formula (i), 0 < x < 0.5 and 0 < y < 0.5 may be satisfied. Also, in some embodiments, 0 < x < 0.3 and 0 < y < 0.3 may be satisfied.
[0018] In some embodiments, the precursor particles 200 are generally spherical, or in some embodiments, the precursor particles 200 may be irregularly shaped, or the like. In this specification, "substantially spherical" refers to a shape that can be regarded as a sphere as a whole, and the average aspect ratio based on a cross-sectional observation image by an electron microscope is approximately 1 to 2, preferably 1 to 1.5, and more preferably 1 to 1.2. In addition, in this specification, "aspect ratio" refers to the value obtained by dividing the long side of the rectangle that has the smallest area among the rectangles circumscribing the outline of the particle by the short side. In addition, "average aspect ratio" refers to the arithmetic average of the aspect ratios of at least 100 randomly selected particles.
[0019] The average particle size of the precursor particles 200 is, for example, 3.0 μm or more, preferably 4.0 μm or more, and more preferably 4.5 μm or more. The average particle size of the precursor particles 200 is, for example, 9.0 μm or less, preferably 7.0 μm or less, and more preferably 5.5 μm or less. In this specification, the term "average particle size" refers to the median diameter (D 50 This refers to particle size, which is the particle size that corresponds to a cumulative frequency of 50 volume % from the small particle side in the volume-based particle size distribution based on the laser diffraction / scattering method.
[0020] The outer shell 210 includes a plurality of primary particles 212. In this embodiment, the outer shell 210 is formed by agglomerating the plurality of primary particles 212 by physical or chemical bonding forces. In this specification, the term "primary particle" refers to the smallest unit of particles constituting the precursor particle 200, and specifically refers to the smallest unit determined from the geometric shape of the appearance.
[0021] The outer shell 210 may have a single-layer structure, or may have a multi-layer structure in which multiple layers are stacked.
[0022] The average thickness of the outer shell 210 may be, for example, 1 / 5 or less, and preferably 1 / 6 or less, of the average particle size of the precursor particles 200. The average thickness of the outer shell 210 may be, for example, 1 / 10 or more, or 1 / 8 or more, of the average particle size of the precursor particles 200. By making the average thickness of the outer shell 210 thinner than the average particle size of the precursor particles 200, the diffusion resistance of Li ions is reduced and the output characteristics are improved. In this specification, the thickness of the outer shell 210 refers to that measured in a cross-sectional observation image of the precursor particle 200 taken by an electron microscope, and the average thickness of the outer shell 210 refers to the arithmetic mean of the thicknesses of the outer shell 210 measured in at least 100 precursor particles 100.
[0023] The shape of the primary particles 212 may be, for example, needle-like, plate-like, elliptical, or the like. The average aspect ratio (length of major axis / length of minor axis) of the precursor particles 200 based on a cross-sectional observation image of the precursor particles 200 under an electron microscope is, for example, 2 or more, preferably 3 or more, and more preferably 5 or more. The longer the average aspect ratio of the primary particles 212, the more the diffusion resistance of Li ions can be reduced. The average aspect ratio of the primary particles 212 may be, for example, 50 or less, 20 or less, or 10 or less.
[0024] The average length of the major axis of the primary particles 212 is, for example, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, or 0.3 μm or more, and the average length of the major axis of the primary particles 212 is, for example, 1.2 μm or less, 1 μm or less, or 0.8 μm or less.
[0025] The average length of the minor axis of the primary particles 212 is, for example, 0.01 μm or more, 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more, and the average length of the minor axis of the primary particles 212 is, for example, 0.6 μm or less, 0.4 μm or less, or 0.2 μm or less.
[0026] The average lengths of the major and minor axes of the primary particles 212 are measured based on an electron microscope cross-sectional observation image of the precursor particle 200. In this specification, the average lengths of the major and minor axes of the primary particles 212 refer to the arithmetic mean of the major and minor axes of at least 100 primary particles 212.
[0027] At least 50% of the primary particles 212 contained in the outer shell 210 are radially oriented from the center of the precursor particle 200 toward the surface of the precursor particle 200. In a preferred embodiment, the oriented primary particles 212 account for at least 60%, more preferably at least 65%, and even more preferably at least 70%. By aligning more primary particles 212 radially, the diffusion resistance of Li ions can be reduced and the output characteristics can be improved. The percentage of the primary particles 212 mentioned above indicates a percentage based on the number, and indicates the percentage of the number of radially oriented primary particles 212 out of the total number (at least 100) of the measured primary particles 212. In this specification, "primary particles are radially oriented" means that the angle between the long axis direction of the primary particle 212 and the reference line connecting the center of the primary particle 212 and the center of the precursor particle 200 is 30° or less. This measurement can be performed by processing the cross section of the precursor particle 200 with an ion beam and observing the cross section with an electron microscope. Alternatively, the orientation can be confirmed by electron backscatter diffraction (EBSD).
[0028] The hollow portion 220 is a space surrounded by the outer shell portion 210. The hollow portion 220 does not have to be completely surrounded by the outer shell portion 210, and includes an embodiment in which a part of the outer shell portion 210 is missing. The number of primary particles in the hollow portion 220 is less than that in the outer shell portion 210, or the hollow portion 220 does not have any primary particles. That is, the ratio of the primary particles 212 contained in the outer shell portion 210 to the primary particles contained in the entire precursor particle 200 can be, for example, 90% or more, 95% or more, 98% or more, or 100%. This makes it possible to obtain an active material that reacts well with Li during firing. In this specification, the proportion of such primary particles is measured based on the area ratio in a cross-sectional SEM.
[0029] 2 is a flow diagram showing an outline of a method for producing a positive electrode active material for use in a lithium ion secondary battery in one embodiment. This production method includes a raw material preparation step S10, a crystallization step S20, a mixing step S30, and a firing step S40. The raw material preparation step S10 and the crystallization step are included in the production process of the precursor particles 200 described above. The production method disclosed here may further include other steps at any stage.
[0030] The raw material preparation step S10 is, for example, a step of preparing raw materials of the precursor material. Examples of the precursor material include a metal compound containing the metal element contained in the precursor particle 200 and an ammonium ion donor. The metal compound containing the metal element contained in the precursor particle 200 may be, for example, a water-soluble salt. For example, sulfates, nitrates, oxalates, etc. may be used as appropriate as the water-soluble salt. These water-soluble salts may be used alone or in combination of two or more. The metal element contained in the precursor particle 200 is, for example, a metal element represented by the above general formula (1) and includes at least Ni.
[0031] In the raw material preparation step S10, for example, the metal compound is dissolved in water to prepare a raw metal aqueous solution having the metal element contained in the precursor particle 200. As the water, from the viewpoint of preventing the inclusion of impurities, ion-exchanged water, distilled water, ultrafiltered water, reverse osmosis water, etc. can be suitably used.
[0032] In the raw material preparation step S10, an ammonium ion donor is prepared. The ammonium ion donor is, for example, an aqueous solution containing ammonia ions. Such an aqueous solution may be purchased commercially (ammonia water), or may be prepared by dissolving a compound that supplies ammonium ions in a solvent containing water. For example, ammonium sulfate, ammonium nitrate, ammonium hydroxide, ammonium halide water, ammonia, etc. may be appropriately used as such a compound. These compounds may be used alone or in combination of two or more. Ammonium ions can promote the generation or growth of nuclei and increase the adhesiveness or adhesion between primary particles in the crystallization step S20 described later. Although not limited thereto, the aqueous solution containing ammonium ions contains, for example, 0.1 wt% to 5 wt%, preferably 0.5 wt% to 2 wt% of ammonium ions.
[0033] In the crystallization step S20, precursor particles are prepared using a crystallizer. The crystallizer is preferably a device capable of generating a Taylor vortex flow in the reaction field. The device for generating a Taylor vortex flow may be a commercially available product. FIG. 3 is a schematic diagram showing a rough configuration of the crystallizer. FIG. 4 is a schematic diagram of a cross section taken along line IV-IV shown in FIG. 3. L and R in FIG. 3 indicate left and right, respectively, but do not limit the installation mode of the crystallizer.
[0034] The crystallization apparatus 300 shown in Fig. 3 includes an outer cylinder 310, an inner cylinder 320, and a motor 322. The crystallization apparatus 300 has a reaction chamber 330 between the outer cylinder 310 and the inner cylinder 320. The reaction chamber 330 is an area where a crystallization reaction takes place and where Taylor vortices are generated. The Taylor vortices refer to the flow of a fluid that generates Taylor vortices. The Taylor vortices refer to a form of vortex that flows in a circular shape.
[0035] In this embodiment, the outer cylinder 310 is cylindrical. The central axis of the outer cylinder 310 extends in the left-right direction in Fig. 3. Here, the outer cylinder 310 is fixed so as not to rotate around the central axis.
[0036] In this embodiment, the outer cylinder 310 is provided with a first supply port 312, a second supply port 314, a third supply port 316, and an exhaust port 318. All of these are in communication with the reaction chamber 330.
[0037] In this embodiment, the first supply port 312 is a portion that supplies a raw metal aqueous solution to the reaction chamber 330. The second supply port 314 is a portion that supplies a pH adjuster to the reaction chamber 330. The third supply port 316 is a portion that supplies an ammonium ion supplier to the reaction chamber 330. Although three supply ports are provided in this embodiment, the number is not particularly limited and may be one, two, or four or more. The type of supply may be different for each supply port, or two or more types of supply may be supplied from one supply port.
[0038] The outlet 318 is provided for discharging the fluid in the reaction chamber 330. The fluid discharged from the outlet 318 contains the precursor particles 200 obtained by the crystallization reaction. This makes it possible to recover the precursor particles 200 from the reaction chamber 330.
[0039] In this embodiment, the inner cylinder 320 is cylindrical. However, the inner cylinder 320 may be cylindrical. The diameter of the inner cylinder 320 is designed to be smaller than the diameter of the outer cylinder 310. The space between the inner diameter of the outer cylinder 310 and the outer diameter of the inner cylinder 320 is the reaction chamber 330. The diameter of the inner cylinder 320 is designed to be large enough to generate a Taylor vortex flow in the reaction chamber 330. The central axis of the inner cylinder 320 extends in the left-right direction of FIG. 3. In this embodiment, the central axis of the inner cylinder 320 is arranged to overlap with the central axis of the outer cylinder 310.
[0040] The inner cylinder 320 is connected to a motor 322 and is designed so that the inner cylinder 320 can rotate clockwise or counterclockwise about its central axis by the motor 322. By rotating the inner cylinder 320, Taylor vortices can be generated in the fluid (e.g., liquid phase) in the reaction chamber 330.
[0041] The rotation speed of the inner cylinder 320 about its central axis is not particularly limited as long as it can generate a Taylor vortex flow, but is, for example, 300 rpm or more, 500 rpm or more, 1000 rpm or more, 1500 rpm or more, or 2000 rpm or more. Also, the rotation speed of the inner cylinder 320 about its central axis is, for example, 3000 rpm or less, 2800 rpm or less, or 2600 rpm or less.
[0042] In order to prepare the precursor particles 200 using the crystallizer 300, for example, a reaction solution containing a metal compound containing a metal element contained in the precursor particles and an ammonium ion donor is prepared in the reaction chamber 330. Such a reaction solution is prepared, for example, by supplying a raw metal aqueous solution and an ammonium ion donor to the reaction chamber 330. Note that a mixture of the raw metal aqueous solution and the ammonium ion donor may be supplied to the reaction chamber 330.
[0043] In the crystallization step S20, it is preferable to adjust the oxygen concentration in the reaction field. The oxygen concentration in the reaction chamber 330 is, for example, 20 vol% or more, and preferably 22 vol% or more. The oxygen concentration in the reaction chamber 330 is, for example, 40 vol% or less, preferably 35 vol% or less, more preferably 30 vol% or less, and even more preferably 25 vol% or less. The more oxygen is supplied to the reaction chamber 330, the higher the ratio of the hollow part of the precursor particle tends to be. That is, the more oxygen is supplied to the reaction chamber 330, the smaller the thickness of the outer shell part relative to the average particle size of the precursor particle can be.
[0044] The pH of the reaction solution at 25°C is, for example, 9 or more, preferably 10.5 or more, more preferably 10.8 or more, even more preferably 11 or more, and particularly preferably 11.4 or more. Although not particularly limited, the pH of the reaction solution at 25°C is, for example, 13.5 or less, preferably 13 or less, more preferably 12.5 or less, and even more preferably 12 or less. In some preferred embodiments, the pH of the reaction solution is maintained constant from the start to the end of the crystallization reaction. Under such conditions, the pH is not changed during the crystallization reaction, so the production efficiency of the precursor particles 200 is improved. Note that the constant pH does not have to be the same pH value exactly, and for example, a change in pH of ±0.3, preferably ±0.2 of the pH at the start of the crystallization reaction is allowed.
[0045] For example, a pH adjuster can be used to adjust the pH of the reaction solution. As the pH adjuster, for example, carbonates, hydroxides, sulfates, etc. of alkali metals or alkaline earth metals can be appropriately used. These pH adjusters may be used alone or in combination of two or more. Among these, the use of hydroxides of alkali metals or alkaline earth metals is preferred, and the use of sodium hydroxide is particularly preferred.
[0046] The reaction liquid contained in the reaction chamber 330 is stirred by rotating the inner cylinder 320 around the central axis. By rotating the inner cylinder 320, Taylor vortices can be generated in the reaction liquid. The Taylor vortices are generated in at least a part of the reaction liquid in the reaction chamber 330. The Taylor vortices may be generated in the entire reaction liquid. For example, the Taylor vortices are generated as a pair of a first Taylor vortex 332 and a second Taylor vortex 334 adjacent thereto. The first Taylor vortex 332 is generated along the circumference of the inner cylinder 320 and has a clockwise vortex in the circumferential direction. The second Taylor vortex 334 is generated along the circumference of the inner cylinder 320 and has a vortex that rotates in the opposite direction (counterclockwise) to the first Taylor vortex in the circumferential direction. The Taylor vortex itself is generated on a ring along the circumference of the inner cylinder 320, but the fluid that forms the Taylor vortex itself moves to the adjacent Taylor vortex (moves from the left to the right in FIG. 3). Therefore, the reaction liquid stirred by the Taylor vortex moves from the supply ports 312 , 314 , and 316 toward the discharge port 318 while crystallization progresses, and the precursor particles 200 can be collected from the discharge port 318 .
[0047] The precursor particles 200 recovered from the reaction chamber 330 can be recovered by, for example, separating the precursor particles 200 by a solid-liquid separation method such as filtration, washing the precursor particles 200 with water or the like, and drying the separated precursor particles 200.
[0048] Although not particularly limited, the reaction time of the crystallization reaction is, for example, 0.1 to 5 hours, preferably 0.3 to 2 hours, and more preferably 0.5 to 1 hour. Here, the reaction time of the crystallization reaction can be measured, for example, as the time from when the raw metal aqueous solution is supplied to the reaction chamber 330 from the first supply port 312 in a state in which the ammonium ion donor is accommodated in the reaction chamber 330 to when the precursor particles 200 are first recovered from the discharge port 318.
[0049] In some preferred embodiments, an ammonium ion supplier is supplied to the reaction chamber 330 before the raw metal aqueous solution is supplied to the reaction chamber 330. At this time, the ammonium ion supplier is preferably adjusted to achieve the oxygen concentration and pH of the reaction solution in the reaction chamber 330 described above. This allows the crystallization reaction to start when the raw metal aqueous solution is supplied from the first supply port 312 to the reaction chamber 330, and therefore the time from the start of the crystallization reaction to the collection of the precursor particles 200 from the outlet 318 can be controlled, making it possible to make the particle size distribution of the precursor particles more uniform.
[0050] In some preferred embodiments, it is preferable to rotate the inner cylinder 320 in the reaction chamber 330 to generate Taylor vortexes in the ammonium ion supplier before supplying the raw metal aqueous solution to the reaction chamber 330. This makes it possible to make the quality of the precursor particles more uniform since the stirring conditions in the reaction chamber 330 are constant from the start of the crystallization reaction until the precursor particles are collected.
[0051] In some preferred embodiments, the rotation speed of the inner cylinder 320 is constant from the start to the end of the crystallization reaction, which suppresses variation in the quality of the precursor particles 200, eliminates the need for complicated operations, and improves production efficiency.
[0052] In some preferred embodiments, the raw metal aqueous solution is continuously supplied to the reaction solution in the reaction chamber 330. This allows the precursor particles 200 obtained by the crystallization reaction to be continuously collected from the outlet 318, improving the production efficiency of the precursor particles. Also, preferably, an ammonium ion donor is continuously supplied to the reaction solution in the reaction chamber 330. This allows the concentration balance between the metal compounds and ammonium ions in the reaction solution in the reaction chamber 330 to be maintained.
[0053] In the mixing step S30, the obtained precursor particles 200 are mixed with a lithium compound. The mixing method is not particularly limited, and for example, a mixture can be obtained by mixing using a known mixing device (e.g., a shaker mixer, a V blender, a ribbon mixer, a Julia mixer, a Lödige mixer, etc.). As the lithium compound, a compound that is converted into an oxide by firing can be used, and for example, lithium carbonate, lithium nitrate, lithium hydroxide, etc. can be appropriately used.
[0054] In the calcination step S40, the mixture obtained above is calcined to obtain a positive electrode active material that is a lithium transition metal composite oxide. The calcination can be performed in a conventionally known calcination furnace. Although not particularly limited, the calcination temperature may be, for example, about 600 to 1000°C. The calcination temperature refers to the temperature inside the calcination furnace. The calcination time may be approximately 1 hour or more, for example, 1 to 48 hours, and preferably 5 to 24 hours. From the viewpoint of enhancing the crystallinity of the resulting oxide, the calcination atmosphere is preferably an oxygen-containing atmosphere, for example, an oxygen atmosphere or an air atmosphere. The oxygen concentration of the oxygen-containing atmosphere is preferably 10% by volume or more, more preferably 18 to 100% by volume.
[0055] A lithium ion secondary battery using the lithium transition metal composite oxide obtained by firing has excellent output characteristics and cycle characteristics. Specific configuration examples of the lithium ion secondary battery will be described below with reference to the drawings.
[0056] FIG. 5 is a cross-sectional view showing a schematic configuration of a lithium ion secondary battery 100 using a fired product of precursor particles 200 according to an embodiment. The lithium ion secondary battery 100 in FIG. 5 is a sealed battery in which a flat wound electrode body 20 and a non-aqueous electrolyte (not shown) are housed in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The positive and negative electrode terminals 42, 44 are electrically connected to the positive and negative electrode current collector plates 42a, 44a, respectively. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum.
[0057] FIG. 6 is a schematic exploded view showing the configuration of the wound electrode body 20. As shown in FIGS. 5 and 6, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separators 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode current collector exposed portion 52a (i.e., a portion where the positive electrode current collector 52 is exposed because the positive electrode active material layer 54 is not formed) and the negative electrode current collector exposed portion 62a (i.e., a portion where the negative electrode current collector 62 is exposed because the negative electrode active material layer 64 is not formed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode current collector exposed portion 52a and the negative electrode current collector exposed portion 62a are joined to the positive electrode current collector plate 42a and the negative electrode current collector plate 44a, respectively.
[0058] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be, for example, an aluminum foil. The positive electrode active material layer 54 contains at least a lithium transition metal composite oxide, which is a calcined product of the precursor particles according to the present embodiment, as a positive electrode active material. The positive electrode active material layer 54 may further contain a conductive material, a binder, and the like. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (such as graphite) may be suitably used. As the binder, for example, polyvinylidene fluoride (PVDF) may be used.
[0059] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be, for example, copper foil. The negative electrode active material layer 64 includes a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon may be used. The negative electrode active material layer 64 may further include a binder, a thickener, or the like. As the binder, for example, styrene butadiene rubber (SBR) or the like may be used. As the thickener, for example, carboxymethyl cellulose (CMC) or the like may be used.
[0060] As the separator 70, various porous sheets similar to those conventionally used in lithium ion secondary batteries can be used, and examples thereof include porous resin sheets made of resins such as polyethylene (PE) and polypropylene (PP). Such porous resin sheets may have a single-layer structure or a multi-layer structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 70 may be provided with a heat-resistant layer (HRL).
[0061] The non-aqueous electrolyte can be the same as that used in conventional lithium ion secondary batteries, and typically, a supporting salt can be contained in an organic solvent (nonaqueous solvent). As the non-aqueous solvent, aprotic solvents such as carbonates, esters, and ethers can be used. Among them, carbonates are preferred because they have a particularly high effect of reducing low-temperature resistance due to the positive electrode material. Examples of carbonates include ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such non-aqueous solvents can be used alone or in appropriate combination of two or more. As the supporting salt, for example, LiPF 6 , LiBF 4 A lithium salt such as lithium bis(fluorosulfonyl)imide (LiFSI) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0062] The nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt described above, such as various additives such as a gas generating agent, a film forming agent, a dispersing agent, and a thickener, as long as the effects of the present invention are not significantly impaired.
[0063] Such a lithium ion secondary battery 100 can be manufactured by a manufacturing method including a positive electrode manufacturing step of manufacturing a positive electrode sheet 50 using the positive electrode active material (lithium transition metal composite oxide) manufactured by the above manufacturing method.
[0064] As a preferred example, a square lithium ion secondary battery having a flat wound electrode body has been described above. However, the lithium transition metal composite oxide, which is a calcined product of the precursor particles according to this embodiment, can also be used for other types of lithium ion secondary batteries according to a known method. For example, a lithium ion secondary battery having a laminated electrode body (i.e., an electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated) can be constructed using the lithium transition metal composite oxide, which is a calcined product of the precursor particles according to this embodiment. In addition, a cylindrical lithium ion secondary battery, a coin-type lithium ion secondary battery, a laminated lithium ion secondary battery, etc. can also be constructed using the lithium transition metal composite oxide, which is a calcined product of the precursor particles according to this embodiment. Furthermore, an all-solid-state secondary battery in which the electrolyte is a solid electrolyte can also be constructed.
[0065] The lithium ion secondary battery 100 can be used for various purposes. Suitable applications include a driving power source mounted on vehicles such as an electric vehicle (BEV; Battery Electric Vehicle), a hybrid electric vehicle (HEV; Hybrid Electric Vehicle), and a plug-in hybrid electric vehicle (PHEV; Plug-in Hybrid Electric Vehicle). The lithium ion secondary battery 100 can also be used as a storage battery for a small power storage device or the like. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of lithium ion secondary batteries 100 are connected in series and / or parallel.
[0066] As described above, specific aspects of the technology disclosed herein include those described in the following sections. Section 1: A precursor of a positive electrode active material used in a lithium ion secondary battery, The transition metal composite hydroxide particles include Ni. The transition metal composite hydroxide particles have an outer shell portion formed by aggregation of primary particles having an average aspect ratio (long axis length / short axis length) of 2 or more based on SEM observation, and a hollow portion surrounded by the outer shell portion, 50% or more of the primary particles are radially oriented from the center of the transition metal composite hydroxide particle toward the surface, A precursor in which 90% or more of the primary particles contained in the entire transition metal composite hydroxide particle are present in the outer shell portion. Item 2: The precursor according to item 1, wherein the average thickness of the outer shell portion is not more than one-sixth of the average particle diameter of the transition metal composite hydroxide particles. Item 3: The transition metal composite hydroxide particles have the general formula: Ni (1-x-y-z) Co x Mn y A z (OH) 2+a (where 0≦x<0.5, 0≦y<0.5, 0≦z≦0.1, 0≦a≦0.5, and x+y+z<1A is at least one element selected from the group consisting of Mg, Ca, V, Cr, Al, Ti, Zr, Nb, Mo, and W) Item 3. The precursor according to item 1 or 2, which is a compound represented by the formula: Item 4: The precursor according to any one of Items 1 to 3, wherein the average length of the major axis of the primary particles is 0.05 μm or more and 1.2 μm or less. Section 5: A method for producing a precursor of a positive electrode active material for use in a lithium ion secondary battery, comprising: Providing a metal compound containing Ni and an ammonium ion donor; preparing an apparatus including an outer cylinder, an inner cylinder disposed inside the outer cylinder, and a reaction chamber disposed between the outer cylinder and the inner cylinder, and rotating the inner cylinder around an axial direction of the inner cylinder to generate Taylor vortexes in a reaction solution that includes the metal compound and the ammonium ion donor contained in the reaction chamber, thereby crystallizing a transition metal composite hydroxide; Including, The pH of the reaction solution at 25°C is 9 or more, The oxygen concentration in the reaction chamber is 20 vol% or more and 50 vol% or less, The rotation speed of the inner cylinder is 300 rpm or more and 3000 rpm or less. Manufacturing method. Item 6: The method according to item 5, wherein the pH of the reaction solution at 25°C is 10.5 or higher and 13 or lower. Section 7: A method for producing a positive electrode active material for use in a lithium ion secondary battery, comprising the steps of: Item 5 or 6. Mixing the precursor obtained by the production method according to item 5 or 6 with a lithium compound; and baking the blended mixture; The manufacturing method includes the steps of: Item 8: A method for producing a lithium ion secondary battery, comprising producing a positive electrode containing the positive electrode active material obtained by the production method according to item 7.
[0067] Test examples relating to the present technology will be described below, however, the present technology is not limited to those shown in the following test examples.
[0068] Example 1 [Precursor crystallization] A crystallizer capable of generating Taylor vortexes in the reaction chamber was used. The general configuration of the crystallizer is similar to that of the crystallizer 300 described above. The oxygen concentration in the 0.1 L reaction chamber was adjusted to 25 vol%, 1 wt% ammonia water was added, and the inner cylinder of the above device was rotated at 2000 rpm to generate Taylor vortex in the ammonia water in the reaction chamber. Next, 30 wt% sodium hydroxide aqueous solution was supplied to the reaction chamber, and the mixed liquid in the reaction chamber was adjusted to pH 12 at a liquid temperature of 25°C. Nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water to prepare a 1 mol / L aqueous solution of raw metals, with a molar ratio of nickel sulfate:cobalt sulfate:manganese sulfate of 60:20:20. The raw metal aqueous solution, 30 wt% sodium hydroxide aqueous solution, and 1 wt% ammonia aqueous solution were supplied to the mixture in which Taylor vortexes were generated in the reaction chamber in a volumetric ratio of 1:1:1, and crystallization was carried out for 30 minutes under a condition of pH 12. The crystallized product was then washed with water, filtered, and dried to obtain a powdered composite hydroxide (precursor). The composite hydroxide obtained above was analyzed by ICP emission spectroscopy.0.6 Co 0.2 Mn 0.2 (OH) 2 It was confirmed that.
[0069] [Active material firing] A lithium compound was mixed with the composite hydroxide so that the molar ratio (Li:M) of lithium (Li) to metal elements other than lithium (M) was 1.1:1. This mixture was calcined in a calcination furnace at 700°C for 5 hours under an oxidizing atmosphere. This produced a positive electrode active material.
[0070] [Preparation of positive electrode plate] The positive electrode active material obtained above was mixed with N-methyl-2-pyrrolidone (NMP) so that the ratio of the conductive material to the binder was 100:1:1 (by weight) to prepare a positive electrode mixture paste. Acetylene black was used as the conductive material. PVDF was used as the binder. The prepared positive electrode mixture paste was applied to a 15 μm aluminum foil and dried, and then pressed to a specified thickness and processed to a specified size to produce a positive electrode plate.
[0071] [Preparation of negative electrode plate] The graphite, SBR, and CMC were mixed in water in a ratio of 100:1:1 (by weight) to prepare a negative electrode mixture paste. The prepared negative electrode mixture paste was applied to copper foil, dried, pressed to a specified thickness, and cut to a specified size to prepare a negative electrode plate.
[0072] [Preparation of non-aqueous electrolyte secondary battery] The prepared positive and negative electrode plates were stacked on top of each other with a separator between them to prepare a laminated electrode body. Leads were attached to the positive and negative electrode plates. The prepared laminated electrode body was housed in an exterior body made of an aluminum laminate sheet, after which a non-aqueous electrolyte was poured in and the opening of the exterior body was sealed to prepare a test cell. The non-aqueous electrolyte was a solvent consisting of EC:FEC:EMC:DMC=15:5:40:40 (by volume) and 1M LiPF as a Li salt. 6 The following were used:
[0073] <SEM Observation of Precursor> After cross-sectioning the particles of the obtained composite hydroxide (precursor particles) with an ion beam, the cross-section of the particles was observed by SEM. The structure of the precursor particles was evaluated by SEM observation. Fig. 7 shows the cross-section SEM image of the precursor particles obtained in Example 1.
[0074] Also, the orientation of the primary particles contained in the outer shell part was confirmed by SEM observation of the cross-section of the particles of the composite hydroxide. Specifically, with respect to the reference line connecting the center of the primary particle and the center of the composite hydroxide particle, those in which the angle formed by the major axis direction of the primary particle is 30° or less were evaluated as being radially oriented. More than 100 primary particles contained in the outer shell part were randomly observed, and the ratio of the radially oriented primary particles was determined. The results are shown in Table 1.
[0075] Also, the thickness of the outer shell part was measured by SEM observation of the cross-section of the particles of the composite hydroxide. The thicknesses of the outer shell parts of more than 100 particles were randomly measured, and their arithmetic mean was determined. The value obtained by dividing the arithmetic mean of the thickness of the outer shell part by the average particle size of the composite hydroxide particles shown below is shown in Table 1 as the "thickness of the outer shell part relative to the average particle size".
[0076] <Analysis of Average Particle Size of Precursor> The average particle size of the composite hydroxide particles was defined as the particle size (D50) corresponding to 50% cumulative in the volume-based particle size distribution measured by a laser diffraction scattering type particle size analyzer.
[0077] <IV Resistance Measurement> In an environment at 25°C, the test cell was charged so that the state of charge (SOC) was 50% and left standing for 1 hour. Then, it was discharged at a current of 5C for 10 seconds. When the OCV voltage immediately before discharge was V0 and the voltage at the 10-second discharge time was V1, Formula: IV resistance = (V0 - V1) / 5C current value was used to determine the IV resistance value. Table 1 shows the results as a ratio based on Comparative Example 1 described later.
[0078] <Measurement of Cycle Capacity Retention Rate> In an environment of 25°C, a CCCV charge of 0.4C_4.2V_0.1C cut was performed, followed by a CC discharge of 0.4C_2.5V cut. This constituted one cycle, and was repeated 250 times. Formula: Capacity at 250th cycle / Capacity at 1st cycle x 100(%) The capacity retention rate was calculated by the above method, and the results are shown in Table 1.
[0079] Example 2 The oxygen concentration in the reaction chamber was changed to 30 vol% from the conditions of the precursor crystallization in Example 1. The rotation speed of the inner cylinder of the crystallizer was changed to 700 rpm. A 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 10.8 at a liquid temperature of 25°C. A powdered composite hydroxide was obtained in the same manner as in Example 1 except for these. The procedure thereafter up to the preparation of the test cell, and the evaluation of the precursor and the test cell were the same as in Example 1 (the same applies to the following examples).
[0080] Example 3 The oxygen concentration in the reaction chamber was changed to 22 vol% from the conditions for precursor crystallization in Example 1. The rotation speed of the inner cylinder of the crystallizer was changed to 2600 rpm. A 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 11.4 at a liquid temperature of 25°C. A 1 mol / L aqueous raw metal solution was prepared so that nickel sulfate: cobalt sulfate: manganese sulfate: zirconium sulfate were in a molar ratio of 59.9:19.9:19.9:0.3. A powdered composite hydroxide was obtained in the same manner as in Example 1, except for the above. The composite hydroxide obtained was found to have a Ni 0.599 Co 0.199 Mn 0.199 Zr 0.003 (OH) 2 It was confirmed that.
[0081] Example 4 The oxygen concentration in the reaction chamber was changed to 22 vol% from the conditions for precursor crystallization in Example 1. In addition, a 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 13.5 at a liquid temperature of 25° C. A powdery composite hydroxide was obtained in the same manner as in Example 1, except for these points.
[0082] Example 5 From the conditions of the precursor crystallization in Example 1, a 30 wt % aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 9 at a liquid temperature of 25° C. A powdery composite hydroxide was obtained in the same manner as in Example 1 except for this.
[0083] Comparative Example 1 The oxygen concentration in the reaction chamber was changed to 10 vol% from the conditions of the precursor crystallization in Example 1. The rotation speed of the inner cylinder of the crystallizer was changed to 1000 rpm. A 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 11.8 at a liquid temperature of 25°C. A powdery composite hydroxide was obtained in the same manner as in Example 1 except for these.
[0084] Comparative Example 2 The rotation speed of the inner cylinder of the crystallizer was changed to 3500 rpm from the conditions of precursor crystallization in Example 1. A powdery composite hydroxide was obtained in the same manner as in Example 1 except for these. In addition, a 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 12.6 at a liquid temperature of 25°C. A powdery composite hydroxide was obtained in the same manner as in Example 1 except for these.
[0085] Comparative Example 3 The oxygen concentration in the reaction chamber was changed to 22 vol% from the conditions of the precursor crystallization in Example 1. The rotation speed of the inner cylinder of the crystallizer was changed to 200 rpm. A 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber so that the mixed liquid in the reaction chamber had a pH of 10.8 at a liquid temperature of 25°C. A powdery composite hydroxide was obtained in the same manner as in Example 1 except for these.
[0086] [Table 1]
[0087] As shown in Table 1 and FIG. 7, it is understood that precursor particles having a hollow structure can be produced by carrying out a crystallization reaction accompanied by stirring by Taylor vortex flow in an oxidizing atmosphere (for example, oxygen concentration of 20 vol% or more). It is also understood that the primary particles constituting the outer shell of the precursor particles produced by this method tend to be radially oriented. It is also understood that a lithium ion secondary battery including a positive electrode active material produced using precursor particles having such a structure has reduced resistance and improved output characteristics.
[0088] Although specific examples of the present technology have been described above in detail, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]
[0089] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet 52 Positive electrode current collector 52a Exposed part of positive electrode current collector 54 Cathode active material layer 60 Negative electrode sheet 62 Negative electrode current collector 62a Exposed part of negative electrode current collector 64 Negative electrode active material layer 70 Separator 100 Lithium-ion secondary battery 200 Precursor particles (transition metal composite hydroxide particles) 210 Outer shell 212 Primary particles 220 Hollow part 300 Crystallizer 310 Outer cylinder 320 Inner cylinder 330 Reaction Chamber
Claims
1. A precursor of a positive electrode active material used in a lithium ion secondary battery, The present invention relates to a transition metal composite hydroxide particle having Ni. The transition metal composite hydroxide particles have an outer shell portion formed by aggregation of primary particles having an average aspect ratio (major axis length / minor axis length) of 2 or more based on SEM observation, and a hollow portion surrounded by the outer shell portion, 50% or more of the primary particles are radially oriented from the center of the transition metal composite hydroxide particle toward the surface, 90% or more of the primary particles contained in the entire transition metal composite hydroxide particles are present in the outer shell portion. Precursor.
2. 2. The precursor according to claim 1, wherein an average thickness of the outer shell portion is not more than one-sixth of an average particle diameter of the transition metal composite hydroxide particles.
3. The transition metal composite hydroxide particles have the general formula: Ni (1-x-y-z) Co x Mn y A z (OH) 2+a (wherein 0≦x<0.5, 0≦y<0.5, 0≦z≦0.1, 0≦a≦0.5, and x+y+z<1; A is at least one element selected from the group consisting of Mg, Ca, V, Cr, Al, Ti, Zr, Nb, Mo, and W). The precursor according to claim 1 , which is a compound represented by the formula:
4. The precursor according to any one of claims 1 to 3, wherein the average length of the major axis of the primary particles is 0.05 µm or more and 1.2 µm or less.
5. A method for producing a precursor of a positive electrode active material for use in a lithium ion secondary battery, comprising: Preparing a metal compound containing Ni and an ammonium ion donor; preparing an apparatus including an outer cylinder, an inner cylinder disposed inside the outer cylinder, and a reaction chamber disposed between the outer cylinder and the inner cylinder, and rotating the inner cylinder around the axial direction of the inner cylinder to generate Taylor vortexes in a reaction solution that includes the metal compound and the ammonium ion donor contained in the reaction chamber, thereby crystallizing a transition metal composite hydroxide; Including, The pH of the reaction solution at 25° C. is 9 or more, The oxygen concentration in the reaction chamber is 20 vol% or more and 50 vol% or less, The rotation speed of the inner cylinder is 300 rpm or more and 3000 rpm or less. Manufacturing method.
6. The method according to claim 5, wherein the pH of the reaction solution at 25°C is 10.5 or more and 13 or less.
7. A method for producing a positive electrode active material for use in a lithium ion secondary battery, comprising the steps of: mixing the precursor obtained by the method according to claim 5 or 6 with a lithium compound; and calcining the mixed mixture; The manufacturing method includes the steps of:
8. A method for producing a lithium ion secondary battery, comprising: preparing a positive electrode containing the positive electrode active material obtained by the method according to claim 7.
Citation Information
Patent Citations
Reactor for producing lithium complex transition metal oxide precursors and method for producing precursors
JP2015506051A
Nickel manganese cobalt composite hydroxide and lithium nickel manganese cobalt composite oxide
JP2022116212A
Positive active material for lithium secondary battery, method of preparing the same, positive electrode for lithium secondary battery including the same, and lithium secondary battery
JP2023008932A
Nonaqueous electrolyte secondary battery positive electrode active material and method for producing same, and nonaqueous electrolyte secondary battery which uses positive electrode active material
WO2019087493A1
Transition metal complex hydroxide particle and manufacturing method therefor, positive electrode active material for nonaqueous electrolyte secondary battery and manufacturing method therefor, and nonaqueous electrolyte secondary battery
JP2016154143A